Conjugated linoleic acid and cardiac health: Oxidative stress and energetic metabolism in standard and sucrose-rich diets - Diniz, Yeda S. [UNESP]; Santos, Priscila P. [UNESP]; Assalin, Heloisa B. [UNESP]; Souza, Gisele A. [UNESP]; Rocha, Katiucha K. H. R. [UNESP]; Ebaid, Geovana Xavier [UNESP]; Seiva, Fabio R. F. [UNESP]; Amauchi, Juliana F. [UNESP]; Novelli Filho, Jose Luiz V. B. [UNESP]; Novelli, Ethel L. B. [UNESP] (Elsevier B.V., 2008)
Studies on conjugated linoleic acid ingestion and its effect on cardiac tissue are necessary for the safe utilization of this compound as supplement for weight loss. Male Wistar 24-rats were divided into four groups (n = 6):(C)given standard chow, water and 0.5 ml saline, twice a week by gavage; (C-CLA)receiving standard chow, water and 0.5 ml of conjugated linoleic acid, twice a week, by gavage; (S)given standard chow, saline by gavage, and 30% sucrose in its drinking water; (S-CLA)receiving standard chow, 30% sucrose in its drinking water and conjugated linoleic acid. After 42 days of treatment S rats had obesity with increased abdominal-circumference, dyslipidemia, oxidative stress and myocardial lower citrate synthase(CS) and higher lactate dehydrogenase(LDH) activities than C. Conjugated linoleic acid had no effects on morphometric parameters in C-CLA, as compared to C, but normalized morphometric parameters comparing S-CLA with S. There was a negative correlation between abdominal adiposity and resting metabolic rate. Conjugated linoleic acid effect, enhancing fasting-VO2/surface area, postprandial-carbohydrate oxidation and serum lipid hydroperoxide resembled to that of the S group. Conjugated linoleic acid induced cardiac oxidative stress in both fed conditions, and triacylglycerol accumulation in S-CLA rats. Conjugated linoleic acid depressed myocardial LDH comparing C-CLA with C, and beta-hydroxyacyl-coenzyme-A dehydrogenase/CS ratio, comparing S-CLA with S. In conclusion, dietary conjugated linoleic acid supplementation for weight loss can have long-term effects on cardiac health. Conjugated linoleic acid, isomers c9, t11 and t10, c12 presented undesirable pro-oxidant effect and induced metabolic changes in cardiac tissue. Nevertheless, despite its effect on abdominal adiposity in sucrose-rich diet condition, conjugated linoleic acid may be disadvantageous because it can lead to oxidative stress and dyslipidemic profile. (c) 2007 Elsevier B.V All rights reserved.
Keywords: conjugated linoleic acid; sucrose; lipid profile; oxidative stress; heart